1983
DOI: 10.1055/s-2007-1005016
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Kinetics with Indium-111 Platelets: Comparison with Chromium-51 Platelets

Abstract: The application of 111In-oxine to platelet labeling has contributed to the understanding of platelet kinetics along three lines: 1. It allows the measurement of new parameters of splenic function, such as the intrasplenic platelet transit time, which has shed new light on the physiology of splenic blood cell handling. 2. It facilitates the measurement of platelet life span in conditions, such as ITP, in which 51Cr may undergo undesirable elution from the platelet as a result of platelet-antibody interaction. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 66 publications
1
24
1
Order By: Relevance
“…idiopathic thrombocytopenic purpura), (ii) consumption after interaction with the abnormal vasculature (e.g. systemic vasculitides or atherosclerotic vascular and heart valve diseases), and (iii) death of senescent platelets after sequestration in the liver and spleen (114,115).…”
Section: Radiolabeling Methodsmentioning
confidence: 99%
“…idiopathic thrombocytopenic purpura), (ii) consumption after interaction with the abnormal vasculature (e.g. systemic vasculitides or atherosclerotic vascular and heart valve diseases), and (iii) death of senescent platelets after sequestration in the liver and spleen (114,115).…”
Section: Radiolabeling Methodsmentioning
confidence: 99%
“…By using dynamic gamma camera scintigraphy of splenic uptake and blood disappearance immediately following injection of ' ' 'In-labelled platelets it has been shown that the distribution of platelets between spleen and blood is consistent with a closed two-compartment model (4,(23)(24)(25). Thus, these data substantiate that circulating and splenic platelets are in dynamic equilibrium with each other and that the splenic platelet pool size is only dependent on two factors, viz.…”
Section: Kuttimentioning
confidence: 61%
“…White blood cells are usually separated by sedimentation of anticoagulated blood, with careful pipetting of the buffy coat. If the plasma is pipetted instead, then platelets will be labeled [72]. If more advanced separation strategies are used, it is possible to specifically label lymphocytes [73], monocytes [74], or eosinophils [75].…”
Section: Cell Traffickingmentioning
confidence: 99%